On certain geometric properties and Hardy spaces of generalized Bessel–Wright function - Nawaz, Muhammad Umar; Raza, Mohsan; Mehrez, Khaled (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.53, 517.58The main objective of the present research is to examine a specific sufficiency criterion for the pre-starlikeness, strong starlikeness, strong convexity, starlikeness, and convexity of the generalized Bessel–Wright function. Furthermore, we determine the conditions for the generalized Bessel–Wright functions to be included in the Hardy spaces, as well as bounded analytic functions. These applications are given in the form of examples and corollaries.